Efficacy and safety of a new combined treatment method of ultraviolet corneal collagen crosslinking in combination with personalized transepithelial photorefractive keratectomy of keratoconus. Pirogovsky protocol - A. A. Golyakov; R. R. Fayzrakhmanov; M. M. Shishkin; Yu. S. Timofeev (Российский офтальмологический журнал)
Purpose. To evaluate the efficacy and safety of our proposed method for treating keratoconus (Pirogov protocol), including patients with a corneal thickness of less than 450 mm, providing for corneal collagen UV crosslinking in combination with personalized transepithelial photorefractive keratectomy (PRK). Material and methods. Sixty patients (60 eyes) aged 30,6 ± 9,5 with progressive keratoconus stages I–II were divided into two groups: group 1 (30 patients, 30 eyes) received the standard Dresden UV crosslinking protocol, while group 2 (30 patients, 30 eyes) received the Pirogov protocol (one-time corneal UV crosslinking and personalized PRK on the Microscan Visum excimer laser). All patients underwent visometry, refractometry, keratometry, keratopachymetry, keratotopography and optical coherence tomography of the cornea before, immediately after treatment and after 1, 3, 6, 12 and 24 months. Results. In the group of patients operated on according to the Pirogov protocol, after 1 month there was a significant (p < 0.05) increase in uncorrected and best-corrected visual acuity relative to baseline values (before surgery 0.11±0.1 and 0.53 ± 0.22; after 1 month 0.48 ± 0.27 and 0.75 ± 0.2, respectively), improvement in refractive indices (spherical equivalent of refraction decreased from –5.08 ± 0.20 D to –1.04 ± 1.56 D) and keratotopographic corneal indices (KCI, KSI, ESI of the anterior corneal surface, SAI, SRI), the values of which remained stable during 2 years of observation. Similar parameters of the control group did not change significantly during the entire observation period. Conclusion. The developed Pirogov protocol for the treatment of progressive keratoconus stages I–II showed safety and high efficiency.